On the Role of Information and Ideological Security the Counter-Strategy Hybrid War in Eurasia - Igor F. Kefeli; Natalia A. Komleva (Евразийская интеграция: экономика, право, политика, 2019)
This article defines the essence of the hybrid warfare phenomenon and studies the main manifestations of this type of war in relation to the post-Soviet States of Central Asia. Comparative and phenomenological research methods are used. The article considers the main technologies of hybrid warfare in the geographical, economic, information-ideological and information-cybernetic spaces of the Central Asian States, as well as well as the ways to confront these technologies. Conclusion: the inclusion of the State ideology in the scope of constitutional rights should be a political decision of the Member States of the CSTO is a response to the challenge posed by space wars hybrid Big Eurasia. To be here and the great work of the CSTO Parliamentary Assembly. Recognition of State ideology not only as the basis for State and public security, but also the spiritual life space devices of the Eurasian Union should become a response to the challenges of hybrid war.